Analysis of quantitative trait loci and candidate gene exploration associated with cold tolerance in rice (Oryza sativa L.) during the seedling stage - Jo, Sumin; Jang, Seong-Gyu; Lee, Sais-Beul; Lee, Ji-Yoon; Cho, Jun-Hyeon; Kang, Ju-Won; Kwon, Yeongho; Lee, So-Myeong; Park, Dong-Soo; Kwon, Soon-Wook; Lee, Jong-Hee (Frontiers in Plant Science, 2025)
Cold stress during the seedling stage significantly threatens rice (Oryza sativa L.) production, specifically in temperate climates. This study aimed to identify quantitative trait loci (QTLs) associated with cold tolerance at the seedling stage. QTL analysis was conducted on a doubled haploid (DH) population derived from a cross between the cold-sensitive indica cultivar 93-11 and the cold-tolerant japonica cultivar Milyang352. Phenotypic analysis was conducted over 2 years (2022–2023) under cold water treatment (13°C) at the Chuncheon Substation, South Korea. Cold tolerance scores were used to classify the DH populations and parental lines. In 2022, three QTLs were identified on chromosomes 3, 10, and 11; in 2023, a single QTL was identified on chromosome 10. The QTL qCTS1022/23 on chromosome 10 was consistently observed across both years, explaining up to 16.06% and 40.55% of the phenotypic variance, respectively. Fine-mapping of qCTS1022/23 narrowed the candidate region to a 300-kb interval containing 44 polymorphic single-nucleotide polymorphisms. Among the candidate genes, Os10g0409400 was significantly expressed in the cold-tolerant japonica parent Milyang352 under cold stress, indicating its role in conferring cold tolerance. These findings offer valuable insights into the genetic mechanisms of cold tolerance and highlight qCTS1022/23 as a potential target for marker-assisted selection in rice breeding programs to enhance cold tolerance.